The 200 m timber tower - A study of the connections in a tall timber structure - Skoglund, Emma; Hedeås, Astrid (My University, 2022)
Building tall has been a rising trend the latest years and the use of timber for tall structures is considerably increasing. With new construction methods, new challenges arises and timber has both advantages and disadvantages compared to other common building materials. One of the large challenges when constructing tall timber buildings is the connections between the load-bearing elements. In this thesis, different types of timber connection designs were studied to see the structural behaviour in terms of load-bearing capacity in the ultimate limit state. The study was executed for the most critical joint that was located in the bottom of the 200 m tall timber building, where the largest normal force appeared. The slotted-in steel plate connection was chosen for further investigation of connection stiffness by performing FE-analyses. Furthermore, a study of how the stiffness was affected by different parameters have been conducted. The analysed parameters were the number of dowels, the dowel dimensions, the number of slotted-in steel plates, the steel plate thicknesses and the distances between the steel plates. The results show that the parameter with the largest impact on the stiffness was the number of steel plates where an increased amount of plates lead to a larger stiffness. The dowel dimension and the number of dowels are dependent on each other and both these parameters had a slightly smaller influence on the stiffness compared to the number of plates. It was determined that a combination of a small dimension and a large amount of dowels gave a larger stiffness. Two parameters that appeared to have small effect on the global stiffness were the thickness of the steel plates and the distance between them. Based on the stiffness investigation, eight new and improved connection proposals were designed and analysed. In order to identify the most optimized alternative the connections were graded with the help of a weighting matrix. The connection with the highest weighted grade was analysed in terms of deflection in the serviceability limit state to make sure that the requirement was fulfilled. The highest graded connection was chosen as the final design proposal for the connections in the 200 m timber tower.
Keywords: Deformation, Displacement, Failure modes, Slotted-in steel plates, Stiff ness, Tall timber structure, Timber, Timber connection.